The long-term efficacy of concomitant maze IV surgery in patients with atrial fibrillation. (June 2018) - Engelsgaard, Camilla Skals; Pedersen, Kenneth Bruun; Riber, Lars Peter; Pallesen, Peter Appel; Brandes, Axel
Abstract: Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia, and associated with increased risk of morbidity and mortality. AF surgery is widely used for rhythm control of AF, but previous studies have shown varying results. This study sought to investigate the long-term efficacy of concomitant maze IV (CMIV) surgery in an unselected AF population and identify predictors of late AF recurrence. Methods: In total 144 consecutive patients, who underwent CMIV between January 2006 and December 2010 were enrolled. By data from electronic medical records, registers, and rhythm prints, late AF recurrences and heart rhythm at latest follow-up were retrospectively registered. All patients still alive were invited to an ambulant follow-up to update rhythm status. Results: During a median (IQR) follow-up of 7.39 (2.67) years, 114 (79.2%) patients had recurrence. The cumulative incidence of sinus rhythm (SR) without antiarrhythmic drugs (AADs) was 52.3% after 1 year. Long-term results after 2, 5 and 7 years were 47.9%, 32.6% and 25.1%, respectively. At latest follow-up 34.7% were in SR off AADs. No difference in 10-year event-free survival stratified by recurrence were found ( p  = 0.678). Contrary, time to death (5.40 vs. 3.43 years, p  = 0.004) revealed death as competing risk event. The Fine-Gray model identified preoperative sustained AF (SAF) (SHR 3.54, 95%CI [2.35;5.32], p  < 0.001), AF duration (1.08, [1.05;1.11], p  < 0.001), and postoperative atrial tachyarrhythmia (ATA) (2.29, [1.21;4.35], p  = 0.011) as predictors. Conclusion: CMIV in the present cohort provided limited long-term success in obtaining SR. SAF, longer AF duration, and postoperative ATA were associated with late AF recurrence.